Transformasi Pendidikan Pesantren di Era Globalisasi: Adaptasi Kurikulum yang Berwawasan Global - Andit Triono; Annisatul Maghfiroh; Maratus Salimah; Rohman Huda (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2022)
Pesantren is a classical Islamic educational institution that is still transforming toward a better civilization. Transformation in pesantren is not something new, but an old thing that must be considered more critically. One of the most essential things in the framework of the transformation of pesantren in this era of globalization is the transformation of the curriculum. Pesantren must be able to design a curriculum that is adaptive to the times and all the things it needs. This is so that pesantren do not move towards conservatism and orthodoxy of Islamic teachings alone, but must be contextual and in harmony with the times. Therefore, pesantren must accommodate several important aspects of the needs of the times into the curriculum in it. It is starting from the foreign language aspect that is needed by the global world to prepare students to have good communication skills when entering a wider competition. Comprehensive literacy aspects so that students have broad insight and views and have all the basic phenomena. Aspects of information and communication technology so that students can use the latest tools. Finally, the cultural aspect, so that students understand and understand the noble culture of the pesantren and their nation.